Fabrication and drug release study of double-layered microparticles of various sizes - Lee, Wei Li (2013)
Double-layered microparticles, composed of poly(D,L-lactide-co-glycolide) (50:50) (PLGA) core and poly(L-lactide) (PLLA) shell, of controllable sizes ranging from several hundred microns to few microns were fabricated using a one-step solvent evaporation method. Metoclopramide monohydrochloride monohydrate (MCA), a hydrophilic drug, was selectively localized in the PLGA core. To achieve the double-layered particles of size approximately 2 µm, the process parameters were carefully manipulated to extend the phase separation time by increasing oil-to-water ratio and saturating the surrounding aqueous phase with solvent. Subsequently, the drug release profiles of the double-layered particles of various sizes were studied. Increased particle size resulted in faster degradation of polymers because of autocatalysis, accelerating the release rate of MCA. Interestingly, the effect of degradation rates, affected by particle sizes, on drug release was insignificant when the particle size was drastically reduced to 2-20 µm in the investigated double-layered particles. This understanding would provide critical insights into how the controllable formation and unique drug release profiles of double-layered particles of various sizes can be achieved.